2022
DOI: 10.1002/advs.202200844
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal III–V Quantum Dot Photodiodes for Short‐Wave Infrared Photodetection

Abstract: Short‐wave infrared (SWIR) image sensors based on colloidal quantum dots (QDs) are characterized by low cost, small pixel pitch, and spectral tunability. Adoption of QD‐SWIR imagers is, however, hampered by a reliance on restricted elements such as Pb and Hg. Here, QD photodiodes, the central element of a QD image sensor, made from non‐restricted In(As,P) QDs that operate at wavelengths up to 1400 nm are demonstrated. Three different In(As,P) QD batches that are made using a scalable, one‐size‐one‐batch reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 52 publications
1
50
0
Order By: Relevance
“…to reduce the concentration of monomers in order to achieve a larger nucleation radius) 105 eventually obtaining larger nuclei and consequently larger InAs QDs. 101 The resulting InAs QDs exhibited a band-edge absorption tunable from 1140 nm to 1400 nm with relatively broad HWHM (∼150 meV).…”
Section: Synthesis Of Colloidal Inas Qdsmentioning
confidence: 99%
See 1 more Smart Citation
“…to reduce the concentration of monomers in order to achieve a larger nucleation radius) 105 eventually obtaining larger nuclei and consequently larger InAs QDs. 101 The resulting InAs QDs exhibited a band-edge absorption tunable from 1140 nm to 1400 nm with relatively broad HWHM (∼150 meV).…”
Section: Synthesis Of Colloidal Inas Qdsmentioning
confidence: 99%
“… 97 In another study, the same group replaced the native, long-chain OAm ligands by a combination of short-chain stabilizers such as n -butylamine and 3-mercapto-1,2-propanediol to enhance the inter-dots charge carrier mobility. 101 Recently, Zhu et al revealed that most of the InAs trap states originate from surface indium vacancies. These can be partially passivated by zinc chloride (ZnCl 2 ) acting as Z-type ligands ( Fig.…”
Section: Surface Chemistry and Trap Passivation Of Inas Qdsmentioning
confidence: 99%
“…Furthermore, state-of-the-art surface treatment has driven infrared photodetection. Figure e and f show the InAs CQD-based photodetector targeting 900 to 1400 nm, respectively. , Besides, group III–V CQDs have also been applied in various fields, such as down-conversion, LEDs, and lasers. ,, Beyond the visible-range LEDs with InP core/shell structure, a NIR-range LED using InAs core/shell has been studied and recently reported a quantum yield of 73% with device EQE of 13% . However, remaining unresolved challenges limit the progress in achieving advanced optoelectronic devices.…”
Section: Recent Research Outlook On Devicesmentioning
confidence: 99%
“…61−64 However, the resulting device often suffered from poor stability and undesired trap states, which limited its further use in various optoelectronic applications. 64,65 The development of strategies for fabricating conducting films is on course, where films fabricated using halide or short organic ligands 22,56,63 with or without fluoride pre-treatment 66 exhibit a mobility of about 10 −2 −10 −5 cm 2 /(V•s). The modest conductivity of group III−V CQD films compared to films of other ionic CQDs or bulk materials may come from the high trap density in the former.…”
Section: ■ Group Iii−v Cqd Surface and Modificationsmentioning
confidence: 99%
See 1 more Smart Citation